Selection of the Optimal Candidate to MitraClip for Secondary Mitral Regurgitation: Beyond Mitral Valve Morphology - Salvatore, Tanya; Ricci, Fabrizio; Dangas, George D.; Rana, Bushra S.; Ceriello, Laura; Testa, Luca; Khanji, Mohammed Y.; Caterino, Anna Laura; Fiore, Corrado; Popolo Rubbio, Antonio; Appignani, Marianna; Di Fulvio, Maria; et al. (Frontiers in Cardiovascular Medicine, 2021)
Secondary mitral regurgitation (MR) occurs despite structurally normal valve apparatus due to an underlying disease of the myocardium leading to disruption of the balance between tethering and closing forces with ensuing failure of leaflet coaptation. In patients with heart failure (HF) and left ventricular dysfunction, secondary MR is independently associated with poor outcome, yet prognostic benefits related to the correction of MR have remained elusive. Surgery is not recommended for the correction of secondary MR outside coronary artery bypass grafting. Percutaneous mitral valve repair (PMVR) with MitraClip implantation has recently evolved as a new transcatheter treatment option of inoperable or high-risk patients with severe MR, with promising results supporting the extension of guideline recommendations. MitraClip is highly effective in reducing secondary MR in HF patients. However, the derived clinical benefit is still controversial as two randomized trials directly comparing PMVR vs. optimal medical therapy in severe secondary MR yielded virtually opposite conclusions. We reviewed current evidence to identify predictors of PMVR-related outcomes in secondary MR useful to improve the timing and the selection of patients who would derive maximal benefit from MitraClip intervention. Beyond mitral valve anatomy, optimal candidate selection should rely on a comprehensive diagnostic workup and a fine-tuned risk stratification process aimed at (i) recognizing the substantial heterogeneity of secondary MR and its complex interaction with the myocardium, (ii) foreseeing hemodynamic consequences of PMVR, (iii) anticipating futility and (iv) improving symptoms, quality of life and overall survival.